The Z-Drugs Zolpidem, Zaleplon, and Eszopiclone Have Varying Actions on Human GABAA Receptors Containing γ1, γ2, and γ3 Subunits - Richter, Grant; Liao, Vivian W. Y.; Ahring, Philip K.; Chebib, Mary (Frontiers in Neuroscience, 2020)
γ-Aminobutyric-acid type A (GABAA) receptors expressing the γ1 or γ3 subunit are only found within a few regions of the brain, some of which are involved in sleep. No known compounds have been reported to selectively target γ1- or γ3-containing GABAA receptors. Pharmacological assessments of this are conflicting, possibly due to differences in experimental models, conditions, and exact protocols when reporting efficacies and potencies. In this study, we evaluated the modulatory properties of five non-benzodiazepine Z-drugs (zaleplon, indiplon, eszopiclone, zolpidem, and alpidem) used in sleep management and the benzodiazepine, diazepam on human α1β2γ receptors using all three γ subtypes. This was accomplished using concatenated GABAA pentamers expressed in Xenopus laevis oocytes and measured via two-electrode voltage clamp. This approach removes the potential for single subunits to form erroneous receptors that could contribute to the pharmacological assessment of these compounds. No compound tested had significant effects on γ1-containing receptors below 10 µM. Interestingly, zaleplon and indiplon were found to modulate γ3-containing receptors equally as efficacious as γ2-containing receptors. Furthermore, zaleplon had a higher potency for γ3- than for γ2-containing receptors, indicating certain therapeutic effects could occur via these γ3-containing receptors. Eszopiclone modulated γ3-containing receptors with reduced efficacy but no reduction in potency. These data demonstrate that the imidazopyridines zaleplon and indiplon are well suited to further investigate potential γ3 effects on sleep in vivo.